-5-(x+2)=-5(1+x)+3

Simple and best practice solution for -5-(x+2)=-5(1+x)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-(x+2)=-5(1+x)+3 equation:


Simplifying
-5 + -1(x + 2) = -5(1 + x) + 3

Reorder the terms:
-5 + -1(2 + x) = -5(1 + x) + 3
-5 + (2 * -1 + x * -1) = -5(1 + x) + 3
-5 + (-2 + -1x) = -5(1 + x) + 3

Combine like terms: -5 + -2 = -7
-7 + -1x = -5(1 + x) + 3
-7 + -1x = (1 * -5 + x * -5) + 3
-7 + -1x = (-5 + -5x) + 3

Reorder the terms:
-7 + -1x = -5 + 3 + -5x

Combine like terms: -5 + 3 = -2
-7 + -1x = -2 + -5x

Solving
-7 + -1x = -2 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-7 + -1x + 5x = -2 + -5x + 5x

Combine like terms: -1x + 5x = 4x
-7 + 4x = -2 + -5x + 5x

Combine like terms: -5x + 5x = 0
-7 + 4x = -2 + 0
-7 + 4x = -2

Add '7' to each side of the equation.
-7 + 7 + 4x = -2 + 7

Combine like terms: -7 + 7 = 0
0 + 4x = -2 + 7
4x = -2 + 7

Combine like terms: -2 + 7 = 5
4x = 5

Divide each side by '4'.
x = 1.25

Simplifying
x = 1.25

See similar equations:

| -4+3(x+4)=5 | | f(x)=750(0.25) | | -4x+1(1-x)=0x+-1(1-x) | | 2-6c-9+9c= | | 5(x-4)=-9(x+3)+41 | | 10/9=8/x | | 70x+20x=3300 | | 8x+5=-115 | | 1x+4(1-x)=4x+1(1-x) | | (3x^3-4x^4)2x^2= | | -5x+3(1-x)=-3x+1(1-x) | | 70s+20r=3300 | | 4/8=6/n | | 2(62.5+-2y)+4y=125 | | |3x-1/4|=2 | | 2x+0(1-x)=-5x+3(1-x) | | 15xy/35yz | | 9x^2-24x-1=0 | | 5x+-4(1-x)=2x+0(1-x) | | 10z^7(6z+3z^4+4)= | | 0=7x^3-24x^2-16x | | 4y+2x=125 | | 1.6*4= | | 8-8x=8-15x | | 6z^4(10z^5-5)= | | 2x+7-8x=-5 | | 32+48x= | | (1/4)e•e^4x=e^5/6 | | x=log15/log3 | | r^2+9=16 | | L(1/4)e•e^4x=e^5/6 | | (4x)(2y+x)(2y-x)=180 |

Equations solver categories